Development of a reproducible method of analysis of iron, zinc and phosphorus in vegetables digests by SEC-ICP-MS. (5th March 2020) - Dell'Aquila, Caterina; Neal, Andrew L.; Shewry, Peter R.
Highlights: Measurements of elements in vegetables digests were carried out by SEC-ICP-MS. Development of a method of analysis of iron, zinc and phosphorus in vegetables. Ammonium nitrate as a buffer gives more stable performance. Abstract: Vegetables contain iron, zinc and phosphorus as complexes with phytates limiting their availability from a vegetarian diet, meaning non-haem iron deficiency anaemia and zinc deficiency immune malfunction are a risk. Although these elements have been analysed previously in biological fluids and cereal using LC-ICP-MS, there is no method suitable for analysing iron, zinc and phosphorus simultaneously in vegetables because of their complex matrix. In this study, we analysed iron, zinc and phosphorus in cabbage, broccoli, pepper, spinach, kale and rocket after a simulated gastrointestinal digestion using a newly optimised SEC-ICP-MS method. Ammonium nitrate, as the mobile phase, and a suitable rinsing regime, allowed good reproducibility and maintenance of the equipment. The method showed good reproducibility and can be easily adapted to other vegetables, as required.